Modelling the environmental and biological cues for the bloom of sergestid shrimp Acetes (Decapoda: Sergestidae) in coastal water of Miri, Sarawak, Malaysian Borneo - Abang Mohammad Hudzaifah Abang Shakawi,; Muhammad Nur Arif Othman,; Ruhana Hassan,; Chen, Cheng Ann (Penerbit Universiti Kebangsaan Malaysia, 2021)
The sergestid shrimp (Acetes spp.) shows the annual peak season from February to April. This krill-like shrimp, locally known as ‘bubok’, is one of the commercially important fisheries in Miri, Sarawak, Malaysian Borneo. Previous researchers had reported patchy data on the environmental factors and Acetes distribution in Miri-Bintulu adjacent areas. Moreover, insufficient analysis has led to the inability to conduct sustainable management strategies for Acetes fisheries. Therefore, this study is designed to explore the mathematical model usage to understand the interaction between selected water quality parameters and zooplankton assemblages with the Acetes population in the coastal water of Miri. Selected temporal biotic and abiotic data were collected using standard methods and later subjected to mathematical time series analysis called the Granger causality test. The results show bi-directional Granger causality between the abundance of Acetes and dissolved oxygen (DO). Interaction between other water quality parameters (temperature, salinity, turbidity, pH, TSS and Chlorophyll a) with the abundance of Acetes has also emerged. The number of zooplankton in the water column, namely Centropages, Euterpina, Oithona rigida, and Oncaea shows a significant causality towards the abundance of Acetes. The findings imply that complex interaction between biotic and abiotic factors exists during the bloom of Acetes in Miri; thus, relevant agencies should step up measures to ensure sustainable management of the coastal areas where Acetes bloom occurs.